Corporate Reporting in Central and Eastern Europe: Issues, Challenges and Research Opportunities. (2nd September 2017) - Albu, Nadia; Albu, Cătălin Nicolae; Filip, Andrei
Abstract: The purpose of this paper, building upon the papers included in this special section of Accounting in Europe on Corporate reporting in CEE countries and on our knowledge of the region, is to broaden out and open up dialogue and debate about how local institutions are evolving and impact the corporate reporting practices in this under-researched region. We begin by discussing the institutional context for conducting research on corporate reporting by entities in Central and Eastern Europe (CEE), within the broader context of emerging, transitional economies. We also reflect on how research conducted on CEE countries can make a relevant contribution to the international literature, and exemplify by summarizing the research questions and findings of the papers included in the special section. A future research agenda emerges, given the gaps in the international literature and the future research implications suggested in the papers constituting the special section.